Zoning of the Southern Buh River Basin Under the Conditions of Spring Flood Formation - A. O. Dokus; ZH. R. Shakirzanova (Людина і довкілля: Проблеми неоекології, 2021)
The Southern Buh river basin is located in three natural zones of Ukraine and is heterogeneous in terms of physical and geographical conditions of river runoff formation.